Complete spontaneous resolution of severe nonimmunological hydrops fetalis with unknown etiology in the second trimester – a case report - Henrich, W.; Heeger, J.; Schmider, A.; Dudenhausen, J.W. (Journal of perinatal medicine, 2002)
The incidence of nonimmunological fetal hydrops is between 1 in 1500 and 1 in 4000. Overall mortality for this condition is about 80%. This report describes a case of prenatally diagnosed hydrops fetalis with severe generalized edema, ascites and pleural effusion of unknown origin at 19 weeks of gestation. No symptoms were found of infections or anemia, no variabilities were observed in fetal blood analysis or in karyotyping. All signs of hydrops resolved completely after 6 weeks without treatment. The pregnancy continued with normal fetal development; labor was induced at 41 weeks of gestation. After vaginal delivery with vacuum extraction the child was completely healthy and demonstrated no signs of remaining hydrops fetalis or any other pathological parameters except an uncritical atrial septal defect type II which healed without any complications within 3 months post delivery.